2016
DOI: 10.1186/s12906-016-1323-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Heshouwuyin in regulating apoptosis of testicular cells in aging rats through mitochondrial pathway

Abstract: BackgroundPolygonum multiflorum has important effects on anti-aging and immunity enhancement. Many traditional Chinese medicine preparations based on Polygonum multiflorum are widely used for the clinical prevention and treatment of aging. However the mechanisms of these herb mixtures are often unknown. This study investigates the effect of Heshouwuyin, a Chinese herbal compound for invigorating the kidney, on the regulation of testicular cells apoptosis in aging rats.MethodsIn this study, 18-month-old Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Furthermore, it has been shown caspase activation is required for intrinsic and extrinsic apoptosis in the testis of rat 34 . The previous study also showed that the expression of caspase-3 and BAX significantly up-regulated in natural aging rat testes 35 . The treatment of vitamin D3 to D-gal-induced aged rat showed up-regulation of BCL2 and down-regulation of BAX and active caspase-3 in the testis, which clearly demonstrated that vitamin D3 regulates apoptosis in the testis during aging to prevent germ cell loss and it might be suggested that deficiency of vitamin D3 or improper signaling of vitamin D3 due to down-regulation of VDR in the testis leads to germ cell loss which could, in turn, leads to decrease in fertility.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, it has been shown caspase activation is required for intrinsic and extrinsic apoptosis in the testis of rat 34 . The previous study also showed that the expression of caspase-3 and BAX significantly up-regulated in natural aging rat testes 35 . The treatment of vitamin D3 to D-gal-induced aged rat showed up-regulation of BCL2 and down-regulation of BAX and active caspase-3 in the testis, which clearly demonstrated that vitamin D3 regulates apoptosis in the testis during aging to prevent germ cell loss and it might be suggested that deficiency of vitamin D3 or improper signaling of vitamin D3 due to down-regulation of VDR in the testis leads to germ cell loss which could, in turn, leads to decrease in fertility.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, the balance between different cells can be maintained by this process, which is essential to spermatogenesis and male reproduction [29]. Aging ultimately leads to a remarkable augmentation of testicular germ cell apoptosis, which is usually observed through primary spermatocytes and the prominently declining number of sperm cells [30]. TUNEL assay results in this study showed that the seminiferous tubules in the aging group were filled with large quantities of apoptotic cells, concentrated in the primary spermatocytes and secondary spermatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induced via the mitochondria-dependent pathway may be triggered by stress, chemical agents and/or drugs (11); it is also regulated by numerous genes (28). Bax and Bcl-2 are important regulators; Bcl-2 has an anti-apoptotic role and Bax has an apoptosis-promoting role (29,30).…”
Section: Discussionmentioning
confidence: 99%